SETTING LOKAL SMPN PADA KAWASAN TERPENCIL DI KABUPATEN TABALONG PROPINSI KALIMANTAN SELATAN - , Firman Mulia, S. S. Sos, Prof. Ir. Sudaryono, M.Eng, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Infrastructure linked patterns of junior high schools in remote areas is the problem formulation in this thesis. As one of the areas in South Kalimantan, District Tabalong have uneven infrastructure, including education. To succeed 9-year compulsory education program, Tabalong equalizes educational infrastructure, one of them by building secondary schools in remote areas. Tabalong districts chosen as the main study site for school drop-out rate is still relatively high, so did the number of children not attending school. Researchers hope the results give a picture of the benefits of local conditions in relation to the concept of regional planning, provide a reference for the government and stakeholders in the context of regional development, as well as contribute to the knowledge to be traced in a more macro. School infrastructure development should pay attention to the environment, especially the concept of human and environmental infrastructure functions using a linear concept for water infrastructure, electricity, traffic, and the like, also the concept for a planar flat surface, as well as the spatial infrastructure. Physical planning related to the educational environment that requires attention to the issue of activities of educational institutions, public demand for educational institutions, planning physical building and process engineering, as well as administrative issues and equipment of school buildings. The task of providing educational facilities to support the goal of providing universal access to education is quite heavy. Approach is needed to make continuous progress more clearly, but also many challenges of implementation. The task was described through the efforts of the government to know how effective programs can be designed and implemented with the intention of providing infrastructure that meets the needs of the school and contribute to the process of teaching and learning. Conditions, the location and nature of the impact of school infrastructure on access and quality of education are also in consideration. The closer the more likely the student to attend, this is due to mileage and security considerations. The better the quality of infrastructure (especially water and sanitation facilities), new student enrollment rates also tend to increase and absenteeism can be reduced further. Better school facilities mean learning outcomes are also improved. School infrastructure should be easily accessible, durable, functional, safe, hygienic and easy to maintain so therefore it needs to be part of the education development strategy. In terms of educational infrastructure, what will have the greatest impact would vary from school to school.